Selection of Impactful Environmental Parameters Using an Integrated Community Feedback System for Environmental Assessment - Shahsavar, Mitra; Ezlin Ahmad Basri, Noor; Nadi, Behzad; Jaafar, Othman (International Journal of Engineering and Technology, 2019)
Environmental assessment (EA) of metropolitan areas is an appropriate method for evaluating civil and environmental engineering problems. Assessing and identifying the environmental pollution in metropolitan areas is of crucial interest, as these are used in decision making for minimizing environmental pollution. The objective of this study is to select most impactful environmental parameters using an integrated feedback to improve decision-making process and management in metropolitan areas for an environmental assessment process. The study started with 71 environmental parameters that were selected from literature study on the basis of the environmental effects on the metropolis. Subsequently, questionnaires were prepared to select the most important (controlling) environmental parameters that affect the metropolis. These questionnaires were distributed to 300 respondents of three groups. Feedback obtained was from 110 respondents (80 citizens, 11 managers, and 19 experts) in metropolitan Tehran, Iran. Statistical Package for Social Science (SPSS) software was then used to analyze the collected data. Twenty-three environmental parameters were selected based on their effects towards the metropolitan areas as a result of the SPSS analysis. These parameters comprised of 3 physical and biological (PB) parameters, 7 operational and technical (OT) parameters, 9 social and cultural (SC) parameters, and 4 economic and political (EP) parameters.Â Â